LINKING STUDENTS"™ SCIENCE LITERACY AND SCIENTIFIC ATTITUDE THROUGH ENVIRONMENTAL LEARNING APPROACH - Utami, Amaira; Dhitareka, Putra Habib; Nurismawati, Riana (Jurnal Pendidikan Matematika dan IPA, 2025)
In this modern era, where environmental challenges are becoming an urgent issue society faces, the need to foster students"™ science literacy and scientific attitude is becoming crucial. Science literacy empowers individuals to make informed decisions, understand the complexities of the natural world, and solve environmental issues. In practical life, a scientific attitude is the tendency to act and behave in a predetermined way when solving challenges. The Environmental learning approach addresses the challenge by connecting scientific concepts to real-world environmental issues, allowing students to explore environmental challenges and equipping them with practical skills. This research focuses on seeking information about students"™ profile of science literacy and scientific attitude through implementing the environmental learning approach and identifies the correlation between them. This research implements a correlation research design. The purposive sampling method is carried out to define the participants of this research, which are 27 students (12 male and 15 female). The data is collected through an observation sheet and ten short answer questions which was analyzed through descriptive statistics and Pearson"™s Correlation Coefficient. The correlation coefficient result show the number of 0.806 and a significance level (p-value) of 0.000 means a positive and strong correlation between students"™ science literacy and scientific attitude. In conclusion, the connection highlights students"™ capability to grasp phenomena and apply scientific concepts when facing environmental problems.